IMPLICATIONS OF THE RIGHT FOR UNITY OF CUSTOMARY LAW COMMUNITIES IN THE MANAGEMENT OF FOREST AREA LAND IN THE REGENCY OF NORTH LOMBOK (STUDY OF LAW NO. 41 YEAR 1999 CONCERNING FORESTRY) - SH, Mawardi, (Jurnal IUS (Kajian Hukum dan Keadilan), 2013)
In case the concept of ârightâ is perceived in an opposite view by the Adat Law community and the country, then every regulation concerning right will be accepted in a different way too. Meanwhile âregulationâ is in the field of the country authority where the Adat Law community forced to obey their regulations. In Law Number 41 concerning Forestry regulated that an Adat Law community has not entitled to manage forestry land as far as their existence has not recognized by the state although the Adat Law community has made a claim that management on forestry land was part of their congenital right and right on their ancestors root that they already have even before the declaration of Indonesiaâs independence. Therefore, its implication caused conflict between the Adat Law community against the state / government keep on growing. The community continues managing the forest as their ancestorâs cultural basic while the state keep forcing their regulation on Adat Law community. In the end the number of violation against regulation of the management of forest resource keep on increasing, hence the forests are no longer a source of public welfare but oppositely has become a source of disaster for the Adat Law community. In this case the solution would be âthe harmonyâ and âbalanceâ of the stateâs regulation on the Adat Law community. Keywords: Right, Forest Management, Law Enforcement.